Religion lessons making their exit from Polish schools is an opportunity for “deschooling” catechesis - Zjawin, Jacek (Bogoslovni vestnik, 2023)
The article presents the current situation of school religion lessons based on the results of a survey carried out at local and national level. The question of students not attending school religion lessons is outlined, and a thesis that this situation is becoming an opportunity to restore their catechetical character is put forward. For this purpose, the philosophy of Fr. Franciszek Blachnicki is recalled, who in the 1960s, facing a similar situation, pointed to opportunities being offered by transferring religion lessons from school to parish. At the same time, the current situation is shown as an opportunity to remove religion lessons from church so that they could become a real alternative to school ethics lessons.
Keywords: Blachnicki, Franciszek; catechesis; dechurching religion lessons; deschooling catechesis; kateheza; odprava pouka verouka iz cerkve; razšolajoča kateheza; school religion lessons; šolski pouk verouka